KEEFEKTIFAN PENGGUNAAN GAMBAR SERI TERHADAP KETERAMPILAN MENULIS SISWA - Rauldatul Husni; Riyadi Saputra; Eni Astuti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2023)
This study aims to determine whether there is or is not the effectiveness of using picture series in writing skills of recount text at tenth grade of SMA N 18 Tebo. The problems of this research is that students cannot distinguish structures in writing recount texts, students cannot communicate their thoughts in writing, students cannot arrange a series of stories sequentially in writing recount texts. The purpose of this research was to determine the effectiveness of using picture series in teaching writing, and whether students taught through picture series got better grades than students taught through conventional methods. This research used quasi-experimental design. The finding show that picture series can enable students to explore ideas so that students are able to be creative and use imagination to write well after seeing picture series. The results of the analysis of the hypothesis test data on the paired sample test with a significant level of 0.05, show that the sig (2-tailed) result is smaller than the equation test data 0.000<0.05. it is assumed that the difference in mean scores between the experimental and control groups is significant, then Ho is concluded that there was a significant effect of picture series learning media on the results of students’ writing skills of recount text.